2019
DOI: 10.1186/s12931-019-1197-5
|View full text |Cite
|
Sign up to set email alerts
|

Identifying tuberculous pleural effusion using artificial intelligence machine learning algorithms

Abstract: Background The differential diagnosis of tuberculous pleural effusion (TPE) is challenging. In recent years, artificial intelligence (AI) machine learning algorithms have started being used to an increasing extent in disease diagnosis due to the high level of efficiency, objectivity, and accuracy that they offer. Methods Data samples on 192 patients with TPE, 54 patients with parapneumonic pleural effusion (PPE), and 197 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Their predictive model obtained 98.3% specificity, 92.2% sensitivity, and AUC of the ROC curve was 0.976 for identifying TPE. Moreover, Ren et al [ 41 ] applied 12 clinical features to design a random forest model, and this model exhibited favorable diagnostic performance for the identification of TPE with a sensitivity of 90.6% and a specificity of 92.3%. They also verified the diagnostic model in the prospective study, and the results indicated that the specificity and sensitivity were 90.0% and 100.0% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their predictive model obtained 98.3% specificity, 92.2% sensitivity, and AUC of the ROC curve was 0.976 for identifying TPE. Moreover, Ren et al [ 41 ] applied 12 clinical features to design a random forest model, and this model exhibited favorable diagnostic performance for the identification of TPE with a sensitivity of 90.6% and a specificity of 92.3%. They also verified the diagnostic model in the prospective study, and the results indicated that the specificity and sensitivity were 90.0% and 100.0% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that DL demonstrated the highest AUC of 0.995 in the train set whereas the prediction efficiency was less satisfactory in the test and validation set. DL method is more sensitive to changes of sample size than ML technique [ 41 ], and DL algorithm requires sufficient samples to obtain high predictive accuracy. The sample sizes in the test and validation sets were relatively small compared with that in the training set.…”
Section: Discussionmentioning
confidence: 99%
“…Although pleural biopsy has a relatively higher diagnostic accuracy [13] , it is invasive and associated with more complications, as well as higher costs. Hence, it is important to design a cost-effective method that is more accurate and less invasive to identify MPE [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Of course, some studies have also attempted to differentiate MPE from BPE using various indexes. In addition to the limited sample sizes, most clinical studies have not established a quick and novel scoring system for physicians to use in clinical practice [14] . More importantly, no investigations used another independent cohort to externally validate their predictive model [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We can hence conclude that the diagnostic accuracy of each single cancer biomarker is relatively modest so that it seems reasonable to suggest that a multi-marker strategy may be a much better approach in MPE diagnostics. Although the development of such algorithms is indeed challenging, artificial intelligence approaches could be an option (139,140). Further studies, such as SIMPLE (141) and DIAPHRAGM (5), are attempting to use this approach for improving the diagnostic accuracy of cancer biomarkers in MPE.…”
Section: Discussionmentioning
confidence: 99%